2016
DOI: 10.3390/md14100193
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Suppression of Mouse Myoblast Cell Line C2C12 Differentiation Varies According to Chondroitin Sulfate Subtype

Abstract: Chondroitin sulfate (CS), a type of glycosaminoglycan (GAG), is a factor involved in the suppression of myogenic differentiation. CS comprises two repeating sugars and has different subtypes depending on the position and number of bonded sulfate groups. However, the effect of each subtype on myogenic differentiation remains unclear. In this study, we spiked cultures of C2C12 myoblasts, cells which are capable of undergoing skeletal muscle differentiation, with one of five types of CS (CS-A, -B, -C, -D, or -E) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…These GAGs were highly soluble in physiological buffers and 1.0 mg/ml of them did not show any toxic effect on HSF cells. In accordance with a recent study [31], these GAGs were added to medium at a concentration of 0.2 mg/ml, unless otherwise noted. TGF-b (2 ng/ ml) and bFGF (10 ng/ml) (to elicit cell responses) were from Avnova and PeproTech, respectively.…”
Section: Reagentsmentioning
confidence: 99%
“…These GAGs were highly soluble in physiological buffers and 1.0 mg/ml of them did not show any toxic effect on HSF cells. In accordance with a recent study [31], these GAGs were added to medium at a concentration of 0.2 mg/ml, unless otherwise noted. TGF-b (2 ng/ ml) and bFGF (10 ng/ml) (to elicit cell responses) were from Avnova and PeproTech, respectively.…”
Section: Reagentsmentioning
confidence: 99%
“…Compared to monosulfated CSs, such as CS-A, -B, and -C, the highly sulfated CSs, such as CS-E and -H, are known to be highly involved in the regulation of cell differentiation by acting on proteins, such as growth factors, and the ECM [ 9 , 10 ]. In fact, previous studies have shown that CS-E has a stronger effect on various cell physiological processes, such as cell differentiation and cell division, during development than other monosulfated CSs [ 23 , 26 , 27 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We had previously reported that CS-E, a hypersulfated CS chain, has the strongest inhibitory effect on myotube formation among CS-A, -B, -C, -D, and -E subtypes [ 33 ]. In this study, we hypothesized that the effects of CS-E on cell adhesion, via N-cadherin, and cytoskeletal reorganization, via cofilin 2, may be one of the mechanisms by which CS-E suppresses myogenesis.…”
mentioning
confidence: 99%
“…CS-treated myoblasts fused, but myotube formation (elongation) was inhibited, and the cells showed a similar circular shape [17]. On the other hand, reducing CS from a culture environment smoothly promotes myodifferentiation [11,19].…”
mentioning
confidence: 99%
“…CS-treated myoblasts fused, but myotube formation (elongation) was inhibited, and the cells showed a similar circular shape [ 17 ]. On the other hand, reducing CS from a culture environment smoothly promotes myodifferentiation [ 11 , 19 ]. Although CS is being recognized as a regulator of the processes of myodifferentiation and myoregeneration, there is little information on CS sulfation and degradation enzymes.…”
mentioning
confidence: 99%